Joel Yiri - Jirapa village, Ghana - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Joel Yiri is a farmer from the village Jirapa in Ghana. He started using pig manure in his fields, which helped improve his maize yields and increased the income. He keeps a firm business approach to farming, which he explains has helped him to revive his drying land. The changes in rainfall patterns means that farmers need to adapt through various methods.